Communication as a Means of Realizing Relationships Among Staff Members - Shkhutina, L.A.; Bimagambetova, L.Zh.; Mun, N.T. (Вестник Карагандинского университета, 2016)
This article covers communication as a means of realizing relationships among staff members. Communication is considered as a vital condition of shaping and developing a society and personality and the way of re- alizing social relationships. The mutual informing of communication subjects implies the adjustment of col- lective activity in terms of which there may be completely specific communicative barriers of social and psychological nature. The authors consider some certain forms of communication, functions and types of communication, means and styles of communication, mechanisms and forms of conveying information.
Keywords: relationship; communication; society; activity; interaction; personality; behavior; information; language; mutual understanding